Solitary Cystic Psoas Muscle Metastasis From Rectosigmoid Adenocarcinoma. (June 2021) - Farraj, Kristen; Im, Jaehyuck; Gonzalez, Luis F.; Lu, Andrew; Portnoy, Reid; Podrumar, Alida
The most common subtype of colon cancer is colorectal adenocarcinoma. Compared with other subtypes, such as signet-ring and mucinous, colorectal adenocarcinoma has been found to have lower rates of metastasis. Approximately 20% of colorectal cancer cases present with metastatic disease on initial evaluation. The most common locations for metastasis are the liver, lung, peritoneum, bone, and extra-regional lymph nodes. Metastatic disease to the skeletal muscle, however, is considerably rare. We present a clinical case of a 52-year-old female found to have a cystic iliopsoas muscle metastasis from rectosigmoid adenocarcinoma, initially classified as an infected fluid collection.